Evaluating Service Satisfaction and Sustainability of the Afya Insurance Scheme in Kuwait: An Exploratory Analysis - Alnashmi M; Bhuiyan NM; AlFaham N; Salman A; AlHumaidi H; Akhtar N (Dove Medical Press, 2024)
Maha Alnashmi,1 Nuzhat Masud Bhuiyan,2 Nour AlFaham,3 Ahmad Salman,4 Hanadi AlHumaidi,1 Nabeel Akhtar1 1Health Informatics and Information Management Department, Faculty of Allied Health Sciences, Kuwait University, Jabriya, Kuwait; 2Department of Environmental Science and Management, School of Health and Life Sciences, North South University, Bashundhara, Bangladesh; 3Gulf University for Science and Technology, Mubarak Al-Abdullah, Kuwait; 4Public Health Practice, College of Public Health, Shadadiya, KuwaitCorrespondence: Nabeel Akhtar, Kuwait University, Faculty of Allied Health Sciences, HIIM Department, Kuwait, Email nabeel.akhtar@ku.edu.kwPurpose: In 2014, the Kuwaiti parliament enacted the private health insurance law for Kuwaiti retirees ie, Afya to enhance service quality for retirees through the involvement of the private sector. The study aimed to comprehensively analyze Afya across three crucial dimensions: efficiency, inclusiveness, effectiveness, and service quality; delivery of services throughout the revenue management cycle; and its long-term sustainability in Kuwait.Methods: Conducted between June 2021 and August 2022, the study employed both web-based and hardcopy questionnaires, reaching a response rate of 78.79% from a random sample of 514 Kuwaiti beneficiaries holding Afya insurance cards. Exclusions were made for those who did not receive cards or declined participation, resulting in analysis of 405 completed surveys.Results: The findings revealed that 95% of participants frequently utilized services from private hospitals, with a corresponding 78.79% satisfaction rate. However, when seeking medical services from government hospitals, respondents often opted to repeat procedures to ensure accurate results and diagnoses. Despite a strong endorsement for enhancing Afya's coverage plan (94%), over half of the respondents suggested a temporary suspension of the scheme to conduct thorough research and alleviate potential financial burdens on the government. Notably, a significant positive correlation (0.578, p < 0.01) was observed between beneficiary satisfaction and their experience with Afya coverage, underscoring the importance of aligning scheme operations with beneficiary needs.Conclusion: Addressing these disparities and improving access to healthcare services for retirees necessitate a thorough reformation of the Afya scheme. To address these challenges, the study recommends comprehensive reform through evidence-based research, enhanced information exchange mechanisms between public and private sectors, and broader coverage targeting younger demographics. These measures are crucial for ensuring the scheme's efficacy, sustainability, and alignment with the evolving healthcare landscape in Kuwait.Keywords: health insurance, health policy, afya insurance scheme, Kuwait